2017
DOI: 10.1097/mph.0000000000000788
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Risk of Disturbed Root Development in Permanent Teeth in Childhood Cancer Survivors Undergoing Cancer Treatment at Older Age

Abstract: Particularly regarding the root abnormality, treatment at elder age may be a risk factor for root developmental disturbances. Risk evaluation, appropriate follow-up, and early detection of dental issues are required for all CCS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 7 publications
0
14
0
Order By: Relevance
“…The tooth roots begin developing at approximately age 3–4 years and continue up to 16 years 25 . Higher prevalence of root stunting in patients treated by the NOPHO ALL‐2000 protocol may reflect the slightly older age of patients in this protocol 26 . The prevalence of tooth agenesis (hypodontia) was low across all NOPHO protocols and lower than in earlier studies 16,27,28 …”
Section: Discussionmentioning
confidence: 81%
“…The tooth roots begin developing at approximately age 3–4 years and continue up to 16 years 25 . Higher prevalence of root stunting in patients treated by the NOPHO ALL‐2000 protocol may reflect the slightly older age of patients in this protocol 26 . The prevalence of tooth agenesis (hypodontia) was low across all NOPHO protocols and lower than in earlier studies 16,27,28 …”
Section: Discussionmentioning
confidence: 81%
“…A total of 13,261 research articles were initially found in the databases after searching for all keywords. After applying the eligibility criteria and removing overlapping studies, 13,228 investigations were excluded, and a total of 33 studies 5 , 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 on the oral and maxillofacial effects of radiotherapy, as assessed by panoramic radiographs, were included. Table 1 summarizes the details of the selected studies.…”
Section: Resultsmentioning
confidence: 99%
“… 9 10 The number of participants evaluated in the sample studied ranged from 8 37 to 176, 31 and the samples included were highly heterogeneous. Patients with head and neck cancer were often included in the investigated samples, 5 17 19 22 24 28 29 30 31 32 33 34 35 36 37 40 as were patients with hematopoietic neoplasms (such as leukemia), 12 18 23 28 33 although those with neck cancer were also studied independently. 38 39 Some studies were exclusively dedicated to patients with oral squamous cell carcinomas, 21 25 32 rhabdomyosarcoma survivors, 10 14 22 patients with osteoradionecrosis, 17 36 40 and patients in whom the outcomes of surgical procedures such as mandibulotomy 11 19 34 or the use of mandible reconstruction methods were investigated.…”
Section: Resultsmentioning
confidence: 99%
“…This is in accordance with most studies reporting younger age at treatment to be a risk factor for the development of hypodontia and microdontia. Although, there is a study in which researchers found no significant association between the age at treatment, which in most cases coincide with the age at diagnosis, and the incidence of hypodontia, enamel defects, and microdontia (Tanaka et al 2017).…”
Section: Crown Defectsmentioning
confidence: 94%
“…Comparing statistical data from 1980s to 2001-10 (Figure 4), as they are presented through the overall WSR for all tumors in children aged 0-14 years, it is evident that there is an increase from 124…”
Section: ιV Epidemiologymentioning
confidence: 97%